Isolating Effects of Temperature and Light on Nutrient Acquisition by Biofilm and Bryophyte Communities in Arctic Spring-Stream Ecosystems - Tori A. Hebert; Adam C. Hensley; Carla L. Atkinson; Jonathan P. Benstead; Alexander D. Huryn (Ecosystems, 2026)

Contemporary Methods for Capturing Juvenile Salmonids in the Marine Environment - Sean C. Godwin; Emma M. Atkinson; Jamieson B. Atkinson; Mackenzie C. Bartlett; William D. P. Duguid; Marc Trudel; Andrew W. Bateman (Fish and Fisheries, 2026)
Anadromous salmonids play vital roles in marine and freshwater ecosystems. The most abundant of these fishes—Pacific salmon ( Oncorhynchus spp.)—are integral to coastal ecosystems and communities across the North Pacific Rim, but numerous populations are experiencing dramatic declines, particularly towards the south of their range. Although many declines have been linked to poor marine survival, the early marine life phase of salmon has historically been difficult to study because of challenges in capturing juvenile salmon once they leave freshwater. Recent advancements in capture methods, refined over decades of research, have greatly expanded our understanding of juvenile Pacific salmon life history. Here, we synthesise and review the literature on the five main capture techniques for juvenile Pacific salmon in the marine environment: beach seine, miniature purse seine, conventional purse seine, microtroll, and rope trawl. We compare gear, selectivity, cost, and fish welfare considerations across methods. Along with demonstrated utility in Pacific salmon research, these methods also have broad—and in some cases unexplored—applicability for studying other salmonids and nearshore marine fishes globally, including invasive populations and Atlantic salmon.

Establishing a basis for recognising marine ‘other effective area-based conservation measures’ (OECMs) in South Africa - SP Kirkman; P Kowalski; SD Holness; LJ Atkinson; R Brand; L Dunga; TP Fairweather; T Goldman; D Marnewick; J Nhleko; R Peter; C Smith; et al. (African Journal of Marine Science, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

The potential role of Antarctic krill faecal pellets in efficient carbon export at the marginal ice zone of the South Orkney Islands in spring - A. Belcher; G. A. Tarling; C. Manno; A. Atkinson; P. Ward; G. Skaret; S. Fielding; S. A. Henson; R. Sanders (Polar Biology, 2017)

Combination paracetamol and ibuprofen for pain relief after oral surgery: a dose ranging study - Hartley C. Atkinson; John Currie; John Moodie; Simon Carson; Steven Evans; James P. Worthington; Leon J. Steenberg; Eileen Bisley; Chris Frampton (European Journal of Clinical Pharmacology, 2015)

Influence of nocturnal and daytime sleep on initial orthostatic hypotension - N. C. S. Lewis; H. Jones; P. N. Ainslie; A. Thompson; K. Marrin; G. Atkinson (European Journal of Applied Physiology, 2015)

Atlantic transport variability at 25° N in six hydrographic sections - C. P. Atkinson; H. L. Bryden; S. A. Cunningham; B. A. King (Ocean Science, 2012)
In January and February 2010, a sixth transatlantic hydrographic section was completed across 25° N, extending the hydrographic record at this latitude to over half a century. In combination with continuous transport measurements made since 2004 at 26.5° N by the Rapid-WATCH project, we reassess transport variability in the 25° N hydrographic record. Past studies of transport variability at this latitude have assumed transport estimates from each hydrographic section to represent annual average conditions. In this study the uncertainty in this assumption is assessed through use of Rapid-WATCH observations to quantify sub-seasonal and seasonal transport variability. Whilst in the upper-ocean no significant interannual or decadal transport variability are identified in the hydrographic record, in the deep ocean transport variability in both depth and potential temperature classes suggests some interannual or decadal variability may have occurred. This is particularly striking in the lower North Atlantic Deep Water where southward transports prior to 1998 were greater than recent transports by several Sverdrups. Whilst a cooling and freshening of Denmark Straits Overflow Water has occurred which is coincident with these transport changes, these water mass changes appear to be density compensated. Transport changes are the result of changing velocity shear in the vicinity of the Deep Western Boundary Current.

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

CNP budgets of a coral-dominated fringing reef at La Réunion, France: coupling of oceanic phosphate and groundwater nitrate - P. Cuet; M. J. Atkinson; J. Blanchot; B. E. Casareto; E. Cordier; J. Falter; P. Frouin; H. Fujimura; C. Pierret; Y. Susuki; C. Tourrand (Coral Reefs, 2011)

Water velocity dependence of phosphate uptake on a coral-dominated fringing reef flat, La Réunion Island, Indian Ocean - P. Cuet; C. Pierret; E. Cordier; M. J. Atkinson (Coral Reefs, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Mapping the phenology of natural vegetation in India using a remote sensing-derived chlorophyll index - C. Jeganathan; J. Dash; P. M. Atkinson (International Journal of Remote Sensing, 2010)

On the seasonal cycles and variability of Florida Straits, Ekman and Sverdrup transports at 26° N in the Atlantic Ocean - C. P. Atkinson; H. L. Bryden; J. J-M. Hirschi; T. Kanzow (Ocean Science, 2010)
Since April 2004 the RAPID array has made continuous measurements of the Atlantic Meridional Overturning Circulation (AMOC) at 26° N. Two key components of this system are Ekman transport zonally integrated across 26° N and western boundary current transport in the Florida Straits. Whilst measurements of the AMOC as a whole are somewhat in their infancy, this study investigates what useful information can be extracted on the variability of the Ekman and Florida Straits transports using the decadal timeseries already available. Analysis is also presented for Sverdrup transports zonally integrated across 26° N. The seasonal cycles of Florida Straits, Ekman and Sverdrup transports are quantified at 26° N using harmonic analysis of annual and semi-annual constituents. Whilst Sverdrup transport shows clear semi-annual periodicity, calculations of seasonal Florida Straits and Ekman transports show substantial interannual variability due to contamination by variability at non-seasonal frequencies; the mean seasonal cycle for these transports only emerges from decadal length observations. The Florida Straits and Ekman mean seasonal cycles project on the AMOC with a combined peak-to-peak seasonal range of 3.5 Sv. The combined seasonal range for heat transport is 0.40 PW. The Florida Straits seasonal cycle possesses a smooth annual periodicity in contrast with previous studies suggesting a more asymmetric structure. No clear evidence is found to support significant changes in the Florida Straits seasonal cycle at sub-decadal periods. Whilst evidence of wind driven Florida Straits transport variability is seen at sub-seasonal and annual periods, a model run from the 1/4° eddy-permitting ocean model NEMO is used to identify an important contribution from internal oceanic variability at sub-annual and interannual periods. The Ekman transport seasonal cycle possesses less symmetric structure, due in part to different seasonal transport regimes east and west of 50 to 60° W. Around 60% of non-seasonal Ekman transport variability occurs in phase section-wide at 26° N and is related to the NAO, whilst Sverdrup transport variability is more difficult to decompose.

The Challenges of Dewatering at the Victor Diamond Mine in Northern Ontario, Canada - L. C. Atkinson; P. G. Keeping; J. C. Wright; Houmao Liu (Mine Water and the Environment, 2010)

Production of transgenic pineapple (Ananas cosmos (L.) Merr.) plants via adventitious bud regeneration - M.-L. Wang; G. Uruu; L. Xiong; X. He; C. Nagai; K. T. Cheah; J. S. Hu; G.-L. Nan; B. S. Sipes; H. J. Atkinson; P. H. Moore; K. G. Rohrbach; et al. (In Vitro Cellular & Developmental Biology - Plant, 2009)

Occurrence and Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in Bolgoda and Beira Lakes, Sri Lanka - K. A. S. Pathiratne; O. C. P. De Silva; David Hehemann; Ian Atkinson; Robert Wei (Bulletin of Environmental Contamination and Toxicology, 2007)

Prevalence and differential host‐specificity of two avian blood parasite genera in the Australo‐Papuan region - JON S. BEADELL; EBEN GERING; JEREMY AUSTIN; JOHN P. DUMBACHER; MIKE A. PEIRCE; THANE K. PRATT; CARTER T. ATKINSON; ROBERT C. FLEISCHER (Molecular Ecology, 2004)
The degree to which widespread avian blood parasites in the genera Plasmodium and Haemoproteus pose a threat to novel hosts depends in part on the degree to which they are constrained to a particular host or host family. We examined the host distribution and host‐specificity of these parasites in birds from two relatively understudied and isolated locations: Australia and Papua New Guinea. Using polymerase chain reaction (PCR), we detected infection in 69 of 105 species, representing 44% of individuals surveyed ( n = 428). Across host families, prevalence of Haemoproteus ranged from 13% (Acanthizidae) to 56% (Petroicidae) while prevalence of Plasmodium ranged from 3% (Petroicidae) to 47% (Ptilonorhynchidae). We recovered 78 unique mitochondrial lineages from 155 sequences. Related lineages of Haemoproteus were more likely to derive from the same host family than predicted by chance at shallow (average LogDet genetic distance = 0, n = 12, P = 0.001) and greater depths (average distance = 0.014, n = 11, P Haemoproteus subclades identified in a maximum likelihood phylogeny, host‐specificity was evident up to parasite genetic distances of 0.029 and 0.007 based on logistic regression. We found no significant host relationship among lineages of Plasmodium by any method of analysis. These results support previous evidence of strong host‐family specificity in Haemoproteus and suggest that lineages of Plasmodium are more likely to form evolutionarily–stable associations with novel hosts.

Patterns of Hermes transposition in Drosophila melanogaster - N. Guimond; D. K. Bideshi; A. C. Pinkerton; P. W. Atkinson; D. A. O'Brochta (Molecular Genetics and Genomics, 2003)

U-series dating of Hoxnian interglacial deposits at Marks Tey, Essex, England - P. J. Rowe; T. C. Atkinson; C. Turner (Journal of Quaternary Science, 1999)

U‐series dating of Hoxnian interglacial deposits at Marks Tey, Essex, England - P. J. Rowe; T. C. Atkinson; C. Turner (Journal of Quaternary Science, 1999)

GUS expression patterns from a tobacco yellow dwarf virus-based episomal vector - P. D. Needham; R. G. Atkinson; B. A. M. Morris; R. C. Gardner; A. P. Gleave (Plant Cell Reports, 1998)

Expression of an engineered cysteine proteinase inhibitor (Oryzacystatin-IΔD86) for nematode resistance in transgenic rice plants - P. Vain; B. Worland; M. C. Clarke; G. Richard; M. Beavis; H. Liu; A. Kohli; M. Leech; J. Snape; P. Christou; H. Atkinson (Theoretical and Applied Genetics, 1998)

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)